CYBERBULLYING AND VIDEOCONFERENCE EFFECTS ON BODY IMAGE DISTURBANCE IN MEDICAL STUDENTS OF YOGYAKARTA - Budi Pratiti; Meliya Nita Sari; Afkar Aulia; Soewadi Soewadi (Universitas Brawijaya, 2022)
Medical students are often expected to have ideal appearance and thus, may be susceptible to body dysmorphic disorder (BDD). Limited data exist about the influence of demographic factors on the severity of BDD in this population, especially during the COVID-19 pandemic. We aimed to understand the association between demographic variables and severity of body image disturbance in Indonesian medical students. Second-year medical students of Islamic University of Indonesia participated in the study (n=116). Participants completed the informed consent form, self-reported demographic questionnaire, Body Image Disturbance Questionnaire (BIDQ), and additional questions about bullying, cyberbullying, videoconference, and COVID-19. Data were analyzed using Pearson’s correlation and linear regression. We found significant correlations between height, female gender, history of being bullied, history of being cyberbullied, history of being body-shamed, history of being sexually-harassed, lack of confidence about appearance during videoconference, and the behavior of comparing appearance during videoconference with total BIDQ score (|r|=0.304-0.433, p=0.000-0.002). Regression analysis showed that only history of being cyberbullied, lack of confidence about appearance during videoconference, and the behavior of comparing appearance during videoconference (p=0.009 – 0.037) significantly predicted BIDQ score. Internet-related factors such as cyberbullying and worrying or comparing appearance during teleconference could significantly affect body image of medical students.